Pendidikan Karakter pada Siswa Pasca Pandemi Covid-19 - Nurhasanah , Enok; Tasia, Fanni Erda; Hamda, Nasmal (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
Education during the Covid-19 Pandemic has hampered the process of forming the character of students at school. The implementation of education has been diverted through the online system so that the role of parents is very central in supervising and educating their children, especially in cultivating character within the family. Character education is an important lesson to be instilled in children so they can live better lives and have character with values that are based on the points of Pancasila. This study uses a literature study approach to determine character education for students in the post-covid-19 pandemic period. Parents who are in family institutions as teachers at home have a strategic and main role in educating students while studying at home. Schools, parents, and the community must work together in efforts to shape the character of students to create harmony in life. So that good coordination is needed between parents, schools, and the community as a supporting factor in the formation of student character.